Cold dark energy constraints from the abundance of galaxy clusters - Heneka, Caroline; Rapetti, David; Cataneo, Matteo; Mantz, Adam B.; Allen, Steven W.; von der Linden, Anja (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We constrain cold dark energy of negligible sound speed using galaxy cluster abundance observations. In contrast to standard quasi-homogeneous dark e